Диффузия лекарственных препаратов из гидрогелевых нанореакторов - Самченко, Ю.М.; Пасмурцева, Н.А.; Ульберг, З.Р. (Видавничий дім "Академперіодика" НАН України, 2007)
Macromolecular therapeutic systems on the base of hydrogelic nanoreactors are developed, and their sorption and diffusion properties are studied.